Data analytics for active girds - Fei, Siqi (Nanyang Technological University, 2023)
The integration of generators reliant on renewable energy sources has witnessed a notable increase in contemporary times, however, it introduces risks such as voltage drops and overloading to power systems. To mitigate such risks, the power flow study is of widely use. In this project, we will delve into the power flow problems and demonstrate the effectiveness of linear regression as a mathematical tool to address these issues by performing evaluation and error analysis research.